Comparative Analysis of Financial Sustainability of Nepalese Microfinance Institutions - Duwal, Bal Ram (Economic Journal of Nepal, 2015)
Microfinance institutions are divided into two campaigns as "Institutionalist" and "Welfarist". The major Target for Institutionalist campaign is cost recovery and maintaining financial self-sufficiency whereas the basic focus of the Welfaristcompaign is on poverty alleviation by providing financial services with lower interest rate, etc. In this paper, the Nepalese Microfinance Institutions (MFIs) are studied from financial sustainability point of view and analyzed whether different modalities of them make differences in their financial performance. In Nepal, there are mainly four different modalities of MFIs in operation viz. The GI-GBB, PI-MFB, FINGOs and Coop. Based on the empirical data, it is proved that the financial performance of Nepalese MFIs varies in accordance with the applied modalities of the MFIs. Except for government initiated microfinance banks, other Nepalese MFIs are financially sustainable and in the context of Nepalese financial market, the Welfarist MFIs still need to cover the poorest of the poor section of the population and to broaden their financial services. The Economic Journal of Nepal, Vol. 35, No. 3, July-September 2012 (Issue N0. 139)